FMRI-based prediction of naltrexone response in alcohol use disorder: a replication study - Bach, Patrick; Weil, Georg; Pompili, Enrico; Hoffmann, Sabine; Hermann, Derik; Vollstädt-Klein, Sabine; Kiefer, Falk; Mann, Karl; Sommer, Wolfgang H. (European archives of psychiatry and clinical neuroscience, 2021)
Pharmacological treatment in alcohol use disorder suffers from modest effect sizes. Efforts have been undertaken to identify patient characteristics that help to select individuals that benefit from pharmacological treatment. Previous studies indicated that neural alcohol cue-reactivity (CR) might provide a marker that identifies patients, which benefit from naltrexone treatment.